2021
DOI: 10.1097/qad.0000000000003152
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lung and human papilloma virus-associated malignancies in HIV-infected patients

Abstract: Objective:Cancers represent one of the leading cause of mortality/morbidity in patients with HIV (PWH) in industrialized countries. The objective of our study was to compare incidence of lung and human papilloma virus (HPV)-related cancers among PWH with general population over the 2010–2017 period.Design:Prospective and multicenter cohort study.Methods:The study included patients with lung and HPV-related cancers from the ANRS CO3 Aquitaine cohort (PWH) and the general population-based cancer registry in Giro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The human papillomavirus (HPV) is a known direct carcinogen which has been shown to have a higher prevalence at various sites in PLHIV [13]. In a study by Sirera et al [14], both HPV DNA (56%) and high risk-HPV DNA (39%) were detected in biopsy specimens of HIV-positive patients presenting with primary lung cancer, thus, hypothesizing a causal association between HPV infection and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…The human papillomavirus (HPV) is a known direct carcinogen which has been shown to have a higher prevalence at various sites in PLHIV [13]. In a study by Sirera et al [14], both HPV DNA (56%) and high risk-HPV DNA (39%) were detected in biopsy specimens of HIV-positive patients presenting with primary lung cancer, thus, hypothesizing a causal association between HPV infection and SCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the Czech Republic, Jaworek et al (2020) did not detect HPV in 80 primary NSCLCs by using qPCR [ 107 ]. In Bordeaux, France, Chaussade et al (2022) reported HPV incidence rate ratios (IRR) of 1.8 [1.4–2.2] in a cohort of HIV-positive patients with lung cancer (incidence rates for 100 000 people per year) [ 108 ]. In Badalona, Spain, Sirena et al (2022) found HPV in 23 out of 41 (56%) lung carcinomas by using qPCR.…”
Section: Epidemiology Of Hpv In Lung Cancermentioning
confidence: 99%